Bo Rothstein, Just Institutions Matter. The Moral and Political Logic of the Universal Welfare State, Cambridge: Cambridge University Press, 1998, 270 s., S 59,95 he., S 19.95 pb. - Balle Hansen, Morten (Politica, 2000)
-